Réponses

Meilleure réponse !
2013-08-17T10:11:47+02:00

   Si on a :      f : x → (x − 1)² (x + 2)

 

   alors           f(−x)  =  [(−x) − 1]² [(−x) + 2]

                              =  [−(x + 1)]² (−x + 2)

                              =  (x + 1)² (−x + 2)

                              =  (x² + 2x + 1) (−x + 2)

                              =  −x³ − 2x² − x + 2x² + 4x + 2

                              =  −x³ + 3x + 2

2013-08-17T11:43:21+02:00

Résoudre f: x => (x - 1)²(x + 2).

 

Déjà, f: x => (x - 1)²(x + 2) s'écrit également f(x) = (x - 1)² (x + 2).

 

Développement :

 

f(−x) =  [(−x) − 1]² [(−x) + 2]

f(-x)  =  [−(x + 1)]² (−x + 2)

f(-x)  =  (x + 1)² (−x + 2)

f(-x)  =  (x² + 2x + 1) (−x + 2)

f(-x)  =  −x³ − 2x² − x + 2x² + 4x + 2

f(-x)  =  −x³ + 3x + 2

 

En espérant t'avoir aidé.